Mislocalization of the MRN complex prevents ATR signaling during adenovirus infection - Carson, C.T; Orazio, N.I; Lee, D.V; Suh, J; Bekker-Jensen, S; Araujo, F.D; Lakdawala, S.S; Lilley, C.E; Bártek, Jiří; Lukáš, Jiří; Weitzman, Michael (EMBO journal, 2009)
The protein kinases ataxia-telangiectasia mutated (ATM) and ATM-Rad3 related (ATR) are activated in response to DNA damage, genotoxic stress and virus infections. Here we show that during infection with wild-type adenovirus, ATR and its cofactors RPA32, ATRIP and TopBP1 accumulate at viral replication centres, but there is minimal ATR activation. We show that the Mre11/Rad50/Nbs1 (MRN) complex is recruited to viral centres only during infection with adenoviruses lacking the early region E4 and ATR signaling is activated. This suggests a novel requirement for the MRN complex in ATR activation during virus infection, which is independent of Mre11 nuclease activity and recruitment of RPA/ATR/ATRIP/TopBP1. Unlike other damage scenarios, we found that ATM and ATR signaling are not dependent on each other during infection. We identify a region of the viral E4orf3 protein responsible for immobilization of the MRN complex and show that this prevents ATR signaling during adenovirus infection. We propose that immobilization of the MRN damage sensor by E4orf3 protein prevents recognition of viral genomes and blocks detrimental aspects of checkpoint signaling during virus infection.
Keywords: DNA vazebné proteiny; Nuclear Proteins; buněčné linie; jaderné proteiny; adenovirové infekce; adenovirové proteiny E4; nádorové supresorové proteiny; sekvence aminokyselin; lidé; Molecular Sequence Data; replikace viru; Protein Transport; Protein Serine-Threonine Kinases; signální transdukce; Adenoviridae Infections; enzymy opravy DNA; Adenovirus E4 Proteins; ATM protein; Amino Acid Sequence; Signal Transduction; DNA Repair Enzymes; Cell Line; transport proteinů; Humans; Cell Cycle Proteins; molekulární sekvence - údaje; Tumor Suppressor Proteins; fosforylace; Multiprotein Complexes; DNA-Binding Proteins; Ataxia Telangiectasia Mutated Proteins; Adenoviridae; Virus Replication; proteiny buněčného cyklu; protein-serin-threoninkinasy; Phosphorylation; multiproteinové komplexy